Note taking vs note making / Muniroh Hamat ... [et al.] - Hamat, Muniroh; Alias, Fadzilawani Astifar; Mahlan, Siti Balqis; Shamsuddin, Maisurah; Ahmad, Nurhafizah (Unit Penerbitan JSKM, 2024)
Taking notes is an important skill for both students and professionals. Note-taking has experienced a digital shift since the emergence of technology. Students nowadays have more options than the traditional approach of taking notes on paper with pencils. Using instructional technology, educators are developing innovative note-taking strategies. Making notes is also common when reading books, journals, and other reference materials for essays, seminars, presentations, theses, and exams. These exercises are also useful for researchers and teachers who desire to succeed in their fields. We use the terms note taking and note making to identify the two processes of listening and reading described above. Note taking is a passive process that is performed by students or listeners during lectures, whereas 'note making' is a more active and concentrated action that is performed after reading a book or article and noting down relevant and required information. Note taking and note creation are two related important academic abilities that students and researchers must develop, but they must be approached with caution for maximum utility. This article discusses the concepts of taking and making notes, outlining the distinctions between them.